A qualitative study on how Swedish organizations deal with workplace bullying. Issue 2 (2nd April 2016) - Kaya Cicerali, Lütfiye; Cicerali, Eyyüb Ensari
Abstract : The ways and means with which organizations handle workplace bullying are not well-known, and research on this topic is very limited. Therefore, this study attempts to provide insights into this issue. Sweden, being the country where workplace-bullying research was born and the first anti-workplace-bullying law was enacted, would possibly provide the best (and the worst) practices to deal with it, as well. For this study, experienced human resources managers from 45 Swedish organizations with more than thousand employees were recruited via Linked-in business networking tool. Personal interviews with the managers were transcribed verbatim. Hermeneutical-phenomenological analysis of the transcripts by two researchers who analyzed the data independently yielded four major themes: (1) absence of specific policies and procedures against workplace bullying, (2) fuzzy portrayal of bullying, (3) mediation as the most frequently used method of intervention, and (4) rarity of bullying at Swedish organizations. The findings were discussed.